ANALYSIS OF FACTORS INFLUENCING RURAL HOUSEHOLDS’ PARTICIPATION IN INLAND FISHERIES: A CASE STUDY OF GREATER TZANEEN LOCAL MUNICIPALITY, LIMPOPO PROVINCE - Jenny POTSISO MOKHAUKHAU; Abenet BELETE; Johannes JAN HLONGWANE; Jabulile ZAMUKUHLE MANYIKE (Prizren Social Science Journal, 2022)
The study investigated factors that influence the participation of rural households in inland fisheries in the Greater Tzaneen Local Municipality of the Limpopo Province. Data was collected from sixty rural households using purposive and simple random sampling techniques. The objectives were to identify and profile the socio-economic characteristics of rural households and, to determine factors that influence the participation of rural households in inland fisheries. Descriptive statistics and Binary logistic model were employed to achieve these objectives. The findings show that only 42% of rural households participate in inland fisheries. Additionally, about 5% of females are reported as participants of inland fisheries in the Mopani District Municipality. Moreover, gender of the household head has a positive influence on participation while, access to credits, type of agricultural activity and source of income had a negative influence. The study recommends that women be motivated to participate in inland fisheries to enhance food security and improve their livelihoods.